Task-Based Language Teaching in the Middle East: Cultural Appropriateness and Learning Outcomes (Journal of International English Research Studies (JIERS), ISSN: 3048-5231, 2025)
Task-Based Language Teaching (TBLT) has gained prominence as an effective pedagogical approach worldwide, yet its implementation in the Middle East presents unique challenges and opportunities shaped by cultural and contextual factors. This study examines the cultural appropriateness of TBLT in Middle Eastern language classrooms and evaluates its impact on learners’ outcomes. By analyzing classroom practices, learner attitudes, and educational norms across diverse Middle Eastern contexts, the research highlights the ways in which cultural values influence task design, learner engagement, and teacher roles. Findings suggest that while TBLT fosters communicative competence and learner autonomy, adaptations are necessary to align tasks with cultural expectations regarding authority, group dynamics, and learning styles. Ultimately, the study advocates for culturally responsive modifications of TBLT to maximize its effectiveness and contribute to improved language proficiency in the region.